Effect of Enzyme Supplementation on the Performance of Broiler Finisher Fed Microdesmis puberula Leaf Meal - Esonu, B.O.; Azubuike, J.C.; Emenalom, O.O.; Etuk, E.B.; Okoli, I.C.; Ukwu, H.; Nneji, C.S. (International Journal of Poultry Science, 2004)
A thirty-five day feeding trial was conducted to evaluate the performance of broiler finishers fed Microdesmis puberula leaf meal supplemented with `SafzymeR` (a cellulolytic enzyme). Microdesmis puberula is a choice tropical browse plant. Three broiler finisher diets were formulated to contain 0.0, 12.5% Microdesmis puberula leaf meal without enzyme. and 12.5% Microdesmis puberula leaf meal with 0.10% enzyme. One hundred and twenty (120) four-week-old Hubbard broiler chicks were divided into three groups of forty (40) birds each and randomly assigned to the three treatment diets in a completely randomized design (CRD). Data were collected on feed intake, body weight gain and feed conversion ratio. There was significant difference (p<0.05) in feed intake between birds on 0.0% leaf meal diet and birds on 12.5% leaf meal diet. Daily body weight gain of birds on leaf meal with enzyme diet did not significantly differ (p>0.05) from birds on leaf meal diets without enzyme supplementation. Birds on 0.0% leaf meal diet recorded the highest daily body weight gain. Feed conversion ratios of all treatment groups were comparable. The result suggests that 0.10% of the enzyme supplementation in diets containing 12.5% Microdesmis puberula leaf meal did not improve the performance of finisher broilers.